2008 IEEE Nuclear Science Symposium Conference Record 2008
DOI: 10.1109/nssmic.2008.4774183
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of waveform sampling for improved signal processing in TOF PET

Abstract: Abstract-The development of fast photodetectors and of fast, high light output scintillation crystals has placed an increased emphasis on the need for fast readout electronics used for TimeOf-Flight (TOF) PET detectors. These improvements have paralleled developments in analog sampling technology that makes fast waveform digitizing of photodetector signals an attractive alternative to custom PCB and IC designs. Waveform digitization offers a flexible means for evaluating and implementing more complex signal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…As has been shown by Kuhn et al (2004), smaller PMTs would eliminate much of this count rate dependence. Pulse shape analysis of digitized signals will, in principle, also reduce the pulse pile-up effects, and work is on-going in this area (Wiener et al 2008). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As has been shown by Kuhn et al (2004), smaller PMTs would eliminate much of this count rate dependence. Pulse shape analysis of digitized signals will, in principle, also reduce the pulse pile-up effects, and work is on-going in this area (Wiener et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…faster and more uniform convergence of iterative reconstructions) (Karp et al 2008), they have nonetheless been shown to be useful to predict global TOF performance gains (Surti et al 2006). Wong et al (1983) also predicted an increased signal-to-noise (SNR) ratio with improved timing resolution, again for uniform distributions and analytical reconstruction. To take further advantage of this TOF benefit, we have developed a TOF-PET system based on LaBr 3 crystals, which have a faster decay time and higher light output than LSO or LYSO; together, these characteristics improve the timing resolution of LaBr 3 over that of LSO or LYSO.…”
Section: Introductionmentioning
confidence: 99%
“…A simulation by Kuhn et al (2005) predicts a CRT of ∼100 ps FWHM for very small crystals. The dependence of CRT on the time pick-off method was tested by Wiener et al (2008) by comparing analogue to digital methods. Although it was originally reported that the CRT with digital waveform sampling was superior, further work has since demonstrated that these measurements are sensitive to the assumptions made about the shape of the signal rising edge, and that the timing resolutions obtained with digital and analogue methods are comparable (private communication).…”
Section: Sipms Versus Pmtsmentioning
confidence: 99%
“…In recent years, there has been considerable community interest in the use of waveform sampling for TOF PET [1], [2], [3], [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%